Effects of a novel Paraburkholderia phage IPK on the phenanthrene degradation efficiency of the PAH-degrading strain Paraburkholderia caledonica Bk - Nieto, Esteban Emanuel (2025)
Phages are a major cause of bacterial mortality, affecting bacterial diversity and ecosystem functioning. However, the impact of phage-host interactions in contaminated environments and their role in pollutant biodegradation have largely been overlooked. We isolated and characterized a novel phage that infects the PAH-degrading bacterium Paraburkholderia caledonica Bk from a polycyclic aromatic hydrocarbon (PAH)-contaminated soil and investigated the effect of different multiplicity of infection (MOI) ratios on the degradation efficiency of phenanthrene. The phage IPK is a temperate phage with a wide pH and temperature tolerance and a burst size of 80 PFU ml⁻1. The phage was classified as a member of the Caudoviricetes and is related to Pseudomonas and Burkholderia phages. However, its low intergenomic similarity indicates that it is a new species. Three auxiliary metabolic genes (AMGs) related to amino acid metabolism and to bacterial growth regulation were identified in the phage genome. The highest multiplicity of infection (MOI 10) showed a rapid recovery of the host density and greater phenanthrene degradation than MOIs ranging from 0.01 to 1. This work highlights the important role of phage-host interactions in modulating the efficiency of pollutant degradation, which could be a key for improving the establishment of inoculants in bioremediation processes.